Response of steel frame filled by prefabricated RC infill walls with eccentric opening: Experimental study. (February 2023) - Sun, Guohua; Hu, Yuehua; Liu, Wenyuan; Yang, Wenxia
Abstract: A steel frame filled by prefabricated RC infill wall (SFRCW) is an effective lateral load-resisting system wherein RC infill walls are embedded inside. The presence of eccentric opening (EO) such as door or window usually significantly reduces the lateral stiffness and strength. In order to accurately evaluate the effect of the EO on the seismic performance of the SFRCW structure, the cyclic quasi-static tests on two, 1/3-scaled, two-story, single-span SFRCW-EO specimens were performed. Both specimens showed the shear-dominated failure mode, moderate ductile behavior, and pinching hysteretic feature. The concrete cracks were induced from the corners of the EO and were attributed to stress concentration phenomena. The initial lateral stiffness was approximately 50 kN/mm, overall ductility ranged from 2.48 to 2.95, and the overstrength factor reached 2.5. The interface slips and separations between RC infill wall and surrounding steel frame in SFRCW-EO specimens were considerably tiny that could be neglected. The flushed end-plate connection, which had the enough rotation capacity and tension-resisting capacity, was an effective partially-restrained (PR) connection used in the SFRCW-EO. The overall seismic behavior of SFRCW-EO was weaker compared to that of the steel frame with solid RC infill walls because it failed by serious concrete crush. In addition, the on-site assembly was more convenient for the SFRCW-EO specimen. Further, strengthening measures such as the use of an embedded beam were essential for ensuring the integrity of infill walls and improving their overall seismic behavior. Highlights: Two steel frame filled by prefabricated RC infill walls with eccentric opening (SFRCW-EO) were tested under cyclic loading. The effect of eccentric opening on seismic behavior were compared to the previous test specimen. Eccentric opening has key influence on its lateral strength, stiffness, and failure mode.